Evaluasi Kesesuaian Lahan untuk Tanaman Padi Ladang di Desa Petetea’a Kecamatan Kulisusu Utara Kabupaten Buton Utara - Arista, Arista; Zulfikar, Zulfikar; Leomo, Sitti; Syaf, Hasbullah; Yusuf, Dewi Nurhayati; Rustam, La Ode (CV. Eduartpia Publisher, 2024)
Petetea'a Village, North Kulisusu District, North buton Regency has potential agricultural land resources that need to be optimized for use, especially for industrial crop commodities such as field rice. This research aims to classify land suitability classes and determine limiting factors and improvement efforts to support field rice production in Petetea'a Village, North Kulisusu District, North Buton Regency. The method used in this research is a direct observation method in the field taking into account the type of soil, slope, land use and type of geology, while the observation method used is drilling. Data from field observations and the results of soil sample analysis in the laboratory were assessed for land suitability using a matching method with plant growth conditions. Of the research show that the land suitability class for fiel rice commodities in Petetea’a Village, North Kulisusu District, North Buton Regency in the quite suitable class (S2), namely in land unit 1, namely in land unit 6 with limiting factors for rooting media, flood danger, land preparation and nutrient retention. The marginal appropriate class (S3) in lan unit 2 has limiting factors in rooting media, land preparation and nutrient retention.land unit 4 is rooting media and nutrien retention, land unit 5 is rooting media and limiting factors in the unsuitable land suitability class (N) in land unit 3 is rooting media and land unit 7 is rooting media and flood hazard. These limiting factors can generally be repaired through efforts to create drainage channels, adding organic materials, planting cover crops on land with a slope of >40 %. This improvement effort increases the suitability class of the land potentially to be quite suitable (S2) on land units 1 and 6, marginally suitable (S3) on land units 2 and 4 and not suitable (N). on land units 3,5 and 7